High-performance acrylate emulsion and preparation method thereof

By introducing functional monomers into the acrylate emulsion, using chain transfer agents and composite emulsifiers, and using efficient redox initiation systems and crosslinking agents, the existing emulsions have solved the performance balance, environmental adaptability and substrate adhesion in existing emulsions. In addition, the preparation and application of high-performance acrylate emulsions have been realized.

CN119390907APending Publication Date: 2025-02-07FOSHAN ROSF TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411682146.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing acrylate emulsions have shortcomings in performance balance, environmental adaptability, substrate adhesion, weather resistance, residual monomer problems and emulsion stability, which limits its development in high-end application fields.

Method used

45-50% main monomer, 35-40% soft monomer, 8-12% functional monomer, 2-4% carboxy functional monomer, 0.2-0.4% chain transfer agent, 1.4 were used. -2.1% composite emulsifier, 0.6-1.0% redox initiation system, 0.5-0.8% crosslinking agent, 0.5-0.8% pH adjuster and residual water, through the synergy of a number of innovative technologies, High performance acrylate emulsions were prepared.

Benefits of technology

Achieved coordinated optimization of multiple properties, including improving substrate adhesion, weathering and mechanical strength, optimizing the molecular weight and particle size distribution of polymers, improving monomer conversion, reducing residual monomers, enhancing the stability of emulsions and Coating properties, adapt to extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148611070000131
    Figure BDA0005148611070000131
Patent Text Reader

Abstract

The invention relates to the technical field of acrylate emulsion, in particular to high-performance acrylate emulsion and a preparation method thereof. Comprising the following components in parts by weight: 45 to 50 parts of a main monomer, 35 to 40 parts of a soft monomer, 8 to 12 parts of a functional monomer, 2 to 4 parts of a carboxyl functional monomer, 0.2 to 0.4 part of a chain transfer agent, 1.4 to 2.1 parts of a compound emulsifier, 0.6 to 1.0 part of a redox initiation system, 0.5 to 0.8 part of a cross-linking agent and 0.5 to 0.8 part of a pH regulator, and the balance to 100 parts by weight of water; wherein the functional monomer is used for improving the adhesive force and weather resistance of the emulsion to a base material; the chain transfer agent is used for controlling molecular weight distribution and particle size distribution of the emulsion; the redox initiation system is used for improving the monomer conversion rate; the cross-linking agent is used for improving the water resistance and mechanical strength of the emulsion after film formation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic ester emulsions, and in particular to a high-performance acrylic ester emulsion and a preparation method thereof. Background Art

[0002] As an important polymer material, acrylic emulsion is widely used in coatings, adhesives, textiles, papermaking and other fields. In recent years, with the continuous improvement of environmental protection requirements and the expansion of application fields, the research and development of high-performance acrylic emulsion has become the focus of the industry.

[0003] The existing technologies mainly focus on the following aspects:

[0004] 1. Selection and optimization of monomer types: Traditional acrylic emulsions mainly use conventional monomers such as methyl methacrylate and butyl acrylate, which have limited performance.

[0005] 2. Improvement of emulsifier system: Anionic or nonionic emulsifiers are commonly used, but a single system is difficult to meet complex application requirements.

[0006] 3. Selection of initiator system: Traditionally, persulfate or azo initiators are used, but the initiator efficiency and temperature adaptability need to be improved.

[0007] 4. Application of cross-linking technology: Self-cross-linking monomers such as N-hydroxymethyl acrylamide are conventionally used, but there may be formaldehyde release problems.

[0008] However, the prior art still has the following problems:

[0009] 1. Performance balance problem: Improving a certain performance (such as water resistance) often leads to a decrease in other performance (such as flexibility), making it difficult to achieve coordinated optimization of multiple performances.

[0010] 2. Insufficient environmental adaptability: In extreme environments such as high temperature and high humidity, the emulsion stability and coating performance are prone to decline.

[0011] 3. Insufficient adhesion to substrates: Especially for low surface energy substrates (such as metals and plastics), the adhesion of existing emulsions often cannot meet the requirements.

[0012] 4. Poor weather resistance: When exposed to outdoor environment for a long time, the coating film is prone to yellowing, powdering and other phenomena.

[0013] 5. Residual monomer problem: The traditional initiation system is not efficient, resulting in a high residual monomer content, affecting product safety and stability.

[0014] 6. Insufficient emulsion stability: stratification, flocculation and other problems are prone to occur during storage and transportation.

[0015] These problems have seriously restricted the development of acrylic emulsions in high-end application fields, and a new type of high-performance acrylic emulsion is urgently needed to solve these technical problems. Summary of the invention

[0016] In view of the above problems, it is of great practical significance and urgent need to develop a high-performance acrylic emulsion and a preparation method thereof that can solve these technical problems at the same time.

[0017] The invention discloses a high-performance acrylic emulsion, comprising the following components:

[0018] 45-50 parts by weight of main monomer, 35-40 parts by weight of soft monomer, 8-12 parts by weight of functional monomer, 2-4 parts by weight of carboxyl functional monomer, 0.2-0.4 parts by weight of chain transfer agent, 1.4-2.1 parts by weight of composite emulsifier, 0.6-1.0 parts by weight of redox initiator system, 0.5-0.8 parts by weight of crosslinker, 0.5-0.8 parts by weight of pH adjuster, and the balance is up to 100 parts by weight of water; wherein the functional monomer is used to improve the adhesion and weather resistance of the emulsion to the substrate; the chain transfer agent is used to control the molecular weight distribution and particle size distribution of the emulsion; the redox initiator system is used to improve the monomer conversion rate; the crosslinker is used to improve the water resistance and mechanical strength of the emulsion after film formation.

[0019] Specifically, the main monomer is methyl methacrylate, the soft monomer is butyl acrylate, the functional monomer is 2-hydroxy-3-phenoxypropyl methacrylate, and the carboxyl functional monomer is methacrylic acid.

[0020] Specifically, the chain transfer agent is thioglycolic acid.

[0021] Specifically, the composite emulsifier includes 0.8-1.2 parts by weight of anionic emulsifier and 0.6-0.9 parts by weight of nonionic emulsifier.

[0022] Specifically, the anionic emulsifier is sodium lauryl sulfate, and the nonionic emulsifier is alkylphenol polyoxyethylene ether.

[0023] Specifically, the redox initiation system includes 0.3-0.5 parts by weight of an oxidative initiator, 0.1-0.2 parts by weight of a reducing agent, and 0.2-0.3 parts by weight of an activator.

[0024] Specifically, the oxidative initiator is ammonium persulfate, the reducing agent is ascorbic acid, and the activator is triethanolamine.

[0025] Specifically, the cross-linking agent is polyethylene glycol diglycidyl ether, and the pH adjuster is ammonia water.

[0026] A method for preparing the high-performance acrylic emulsion comprises the following steps:

[0027] (1) mixing the main monomer, the soft monomer, the functional monomer and the carboxyl functional monomer, adding the chain transfer agent, and stirring to obtain a monomer mixture A;

[0028] (2) dissolving the composite emulsifier in 80% of the water and stirring to obtain an emulsifier solution B;

[0029] (3) slowly adding the monomer mixture A to the emulsifier solution B, and emulsifying at high speed for 10-15 minutes to obtain a pre-emulsion C;

[0030] (4) adding 10% of the pre-emulsion C and 10% of the water into the reaction kettle and heating the kettle to 75-80° C.;

[0031] (5) dissolving the oxidizing initiator in the redox initiation system in 5% of the water and slowly adding the solution to the reaction kettle to start polymerization;

[0032] (6) simultaneously adding the remaining pre-emulsion C and the aqueous solution of the reducing agent and the activating agent in the redox initiation system to the reaction kettle, and controlling the adding time to be 3-4 hours;

[0033] (7) After the addition is complete, keep the reaction warm for 1 hour;

[0034] (8) cooling to 50° C., adding the cross-linking agent, and reacting for 30 minutes;

[0035] (9) Cooling to room temperature, and adjusting the pH to 7.5-8.5 with the pH adjuster.

[0036] The invention also discloses application of the high-performance acrylic ester emulsion in coatings, adhesives or waterproof materials.

[0037] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0038] 1. Multifunctional monomer synergistic effect: By introducing 2-hydroxy-3-phenoxypropyl methacrylate (HPMA), multiple properties are optimized synergistically. The hydroxyl group of HPMA provides excellent substrate adhesion, especially for low surface energy substrates; while the phenoxy group enhances weather resistance and water resistance. At the same time, its special molecular structure helps to increase the Tg of the polymer, thereby improving the mechanical strength of the coating.

[0039] 2. Precise molecular weight control: Thioglycolic acid, as an efficient chain transfer agent, can precisely control the molecular weight distribution of the polymer. This not only helps to obtain the ideal emulsion particle size distribution (average particle size 98-110nm, PDI <0.06), but also optimizes the balance of mechanical properties of the polymer (tensile strength 18.5-22.8MPa, elongation at break 270-290%).

[0040] 3. High-efficiency initiation system: The ternary redox initiation system (ammonium persulfate / ascorbic acid / triethanolamine) can efficiently initiate polymerization at a relatively low temperature, significantly improving the monomer conversion rate and reducing residual monomers. This not only improves the safety of the product, but also improves the stability of the emulsion and the coating performance.

[0041] 4. Innovative cross-linking technology: Polyethylene glycol diglycidyl ether is used as a post-cross-linking agent, which reacts with the hydroxyl group of HPMA during the film-forming process to form a three-dimensional network structure. This cross-linking method not only avoids the formaldehyde release problem that may exist in traditional self-cross-linking monomers, but also significantly improves the water resistance (rating 5 / 5) and weather resistance (gloss retention rate > 92%) of the coating.

[0042] 5. Optimize the emulsifier system: The combined use of anionic (sodium dodecyl sulfate) and nonionic (alkylphenol polyoxyethylene ether) emulsifiers significantly improves the stability of the emulsion. This synergistic effect not only helps to obtain the ideal particle size distribution, but also improves the wettability of the emulsion to different substrates, thereby improving the adhesion (reaching level 4-5 on both metal and plastic substrates).

[0043] 6. Excellent comprehensive performance: Through the synergistic effect of the above innovations, the high-performance acrylic emulsion of the present invention has excellent performance in water resistance, adhesion, weather resistance and mechanical properties. In particular, it can still maintain excellent performance in extreme environments (such as high temperature and humidity, UV radiation, etc.), greatly expanding its application range.

[0044] In summary, the present invention successfully solves multiple technical problems faced by existing acrylic emulsions through the synergistic effect of multiple innovative technologies, and achieves comprehensive improvement and balance of performance. This high-performance acrylic emulsion has broad application prospects in the fields of high-end coatings, special adhesives, functional films, etc., and is expected to promote the technological upgrading and sustainable development of related industries. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] Preparation of a high performance acrylic emulsion

[0048] The high performance acrylic emulsion of the present embodiment comprises the following components:

[0049] 45 parts by weight of methyl methacrylate, 35 parts by weight of butyl acrylate, 8 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate, 2 parts by weight of methacrylic acid, 0.2 parts by weight of thioglycolic acid, 0.8 parts by weight of sodium lauryl sulfate, 0.6 parts by weight of alkylphenol polyoxyethylene ether, 0.3 parts by weight of ammonium persulfate, 0.1 parts by weight of ascorbic acid, 0.2 parts by weight of triethanolamine, 0.5 parts by weight of polyethylene glycol diglycidyl ether, 0.5 parts by weight of aqueous ammonia, and the balance to 100 parts by weight of water.

[0050] The preparation method comprises the following steps:

[0051] (1) 45 parts by weight of methyl methacrylate, 35 parts by weight of butyl acrylate, 8 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate and 2 parts by weight of methacrylic acid were mixed, 0.2 parts by weight of thioglycolic acid was added, and the mixture was stirred for 10 minutes to obtain a monomer mixture A;

[0052] (2) dissolving 0.8 parts by weight of sodium lauryl sulfate and 0.6 parts by weight of alkylphenol polyoxyethylene ether in 80 parts by weight of water, and stirring for 15 minutes to obtain an emulsifier solution B;

[0053] (3) slowly adding the monomer mixture A to the emulsifier solution B, and high-speed shearing emulsification at a speed of 3000 rpm for 10 minutes to obtain a pre-emulsion C;

[0054] (4) Add 10% pre-emulsion C and 10 parts by weight of water into the reaction kettle and heat it to 75° C.;

[0055] (5) dissolving 0.3 parts by weight of ammonium persulfate in 5 parts by weight of water, and slowly adding the mixture dropwise to the reactor over 15 minutes to start polymerization;

[0056] (6) adding the remaining pre-emulsion C and an aqueous solution of 0.1 parts by weight of ascorbic acid and 0.2 parts by weight of triethanolamine (dissolved in 5 parts by weight of water) to the reactor dropwise for 3 hours;

[0057] (7) After the addition is complete, keep the reaction warm for 1 hour;

[0058] (8) cooling to 50° C., adding 0.5 parts by weight of polyethylene glycol diglycidyl ether, and reacting for 30 minutes;

[0059] (9) Cool to room temperature and adjust the pH to 7.5 with 0.5 parts by weight of aqueous ammonia.

[0060] Example 2

[0061] Preparation of a high performance acrylic emulsion

[0062] The high performance acrylic emulsion of the present embodiment comprises the following components:

[0063] 47.5 parts by weight of methyl methacrylate, 37.5 parts by weight of butyl acrylate, 10 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate, 3 parts by weight of methacrylic acid, 0.3 parts by weight of thioglycolic acid, 1 part by weight of sodium lauryl sulfate, 0.75 parts by weight of alkylphenol polyoxyethylene ether, 0.4 parts by weight of ammonium persulfate, 0.15 parts by weight of ascorbic acid, 0.25 parts by weight of triethanolamine, 0.65 parts by weight of polyethylene glycol diglycidyl ether, 0.65 parts by weight of aqueous ammonia, and the balance to 100 parts by weight of water.

[0064] The preparation method comprises the following steps:

[0065] (1) 47.5 parts by weight of methyl methacrylate, 37.5 parts by weight of butyl acrylate, 10 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate and 3 parts by weight of methacrylic acid were mixed, 0.3 parts by weight of thioglycolic acid was added, and the mixture was stirred for 12 minutes to obtain a monomer mixture A;

[0066] (2) dissolving 1 part by weight of sodium lauryl sulfate and 0.75 parts by weight of alkylphenol polyoxyethylene ether in 80 parts by weight of water, and stirring for 20 minutes to obtain an emulsifier solution B;

[0067] (3) slowly adding the monomer mixture A to the emulsifier solution B, and high-speed shearing emulsification at a speed of 3500 rpm for 12 minutes to obtain a pre-emulsion C;

[0068] (4) adding 10% of pre-emulsion C and 10 parts by weight of water into a reaction kettle and heating it to 77° C.;

[0069] (5) dissolving 0.4 parts by weight of ammonium persulfate in 5 parts by weight of water, and slowly adding the mixture dropwise to the reactor over 20 minutes to start polymerization;

[0070] (6) adding the remaining pre-emulsion C and an aqueous solution of 0.15 parts by weight of ascorbic acid and 0.25 parts by weight of triethanolamine (dissolved in 5 parts by weight of water) to the reactor dropwise for 3.5 hours;

[0071] (7) After the addition is complete, keep the reaction warm for 1 hour;

[0072] (8) cooling to 50° C., adding 0.65 parts by weight of polyethylene glycol diglycidyl ether, and reacting for 30 minutes;

[0073] (9) The mixture was cooled to room temperature and the pH was adjusted to 8.0 with 0.65 parts by weight of aqueous ammonia.

[0074] Example 3

[0075] Preparation of a high performance acrylic emulsion

[0076] The high performance acrylic emulsion of the present embodiment comprises the following components:

[0077] 50 parts by weight of methyl methacrylate, 40 parts by weight of butyl acrylate, 12 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate, 4 parts by weight of methacrylic acid, 0.4 parts by weight of thioglycolic acid, 1.2 parts by weight of sodium lauryl sulfate, 0.9 parts by weight of alkylphenol polyoxyethylene ether, 0.5 parts by weight of ammonium persulfate, 0.2 parts by weight of ascorbic acid, 0.3 parts by weight of triethanolamine, 0.8 parts by weight of polyethylene glycol diglycidyl ether, 0.8 parts by weight of aqueous ammonia, and the balance to 100 parts by weight of water.

[0078] The preparation method comprises the following steps:

[0079] (1) 50 parts by weight of methyl methacrylate, 40 parts by weight of butyl acrylate, 12 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate and 4 parts by weight of methacrylic acid were mixed, 0.4 parts by weight of thioglycolic acid was added, and the mixture was stirred for 15 minutes to obtain a monomer mixture A;

[0080] (2) dissolving 1.2 parts by weight of sodium lauryl sulfate and 0.9 parts by weight of alkylphenol polyoxyethylene ether in 80 parts by weight of water, and stirring for 25 minutes to obtain an emulsifier solution B;

[0081] (3) slowly adding the monomer mixture A to the emulsifier solution B, and high-speed shearing emulsification at a speed of 4000 rpm for 15 minutes to obtain a pre-emulsion C;

[0082] (4) adding 10% pre-emulsion C and 10 parts by weight of water into a reaction kettle and heating it to 80° C.;

[0083] (5) dissolving 0.5 parts by weight of ammonium persulfate in 5 parts by weight of water, and slowly adding the mixture dropwise to the reactor over 25 minutes to start polymerization;

[0084] (6) adding the remaining pre-emulsion C and an aqueous solution of 0.2 parts by weight of ascorbic acid and 0.3 parts by weight of triethanolamine (dissolved in 5 parts by weight of water) to the reactor dropwise simultaneously, and controlling the dropping time to be 4 hours;

[0085] (7) After the addition is complete, keep the reaction warm for 1 hour;

[0086] (8) cooling to 50° C., adding 0.8 parts by weight of polyethylene glycol diglycidyl ether, and reacting for 30 minutes;

[0087] (9) The mixture was cooled to room temperature and the pH was adjusted to 8.5 with 0.8 parts by weight of aqueous ammonia.

[0088] Example 4

[0089] Preparation of a high performance acrylic emulsion

[0090] The high performance acrylic emulsion of the present embodiment comprises the following components:

[0091] 48 parts by weight of methyl methacrylate, 38 parts by weight of butyl acrylate, 11 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate, 3.5 parts by weight of methacrylic acid, 0.35 parts by weight of thioglycolic acid, 1.1 parts by weight of sodium lauryl sulfate, 0.8 parts by weight of alkylphenol polyoxyethylene ether, 0.45 parts by weight of ammonium persulfate, 0.18 parts by weight of ascorbic acid, 0.28 parts by weight of triethanolamine, 0.7 parts by weight of polyethylene glycol diglycidyl ether, 0.7 parts by weight of aqueous ammonia, and the balance to 100 parts by weight of water.

[0092] The preparation method comprises the following steps:

[0093] (1) 48 parts by weight of methyl methacrylate, 38 parts by weight of butyl acrylate, 11 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate and 3.5 parts by weight of methacrylic acid were mixed, 0.35 parts by weight of thioglycolic acid was added, and the mixture was stirred for 13 minutes to obtain a monomer mixture A;

[0094] (2) dissolving 1.1 parts by weight of sodium lauryl sulfate and 0.8 parts by weight of alkylphenol polyoxyethylene ether in 80 parts by weight of water, and stirring for 22 minutes to obtain an emulsifier solution B;

[0095] (3) slowly adding the monomer mixture A to the emulsifier solution B, and high-speed shearing emulsification at a speed of 3800 rpm for 13 minutes to obtain a pre-emulsion C;

[0096] (4) adding 10% of pre-emulsion C and 10 parts by weight of water into a reaction kettle and heating it to 78° C.;

[0097] (5) dissolving 0.45 parts by weight of ammonium persulfate in 5 parts by weight of water, and slowly adding the mixture dropwise to the reactor over 22 minutes to initiate polymerization;

[0098] (6) adding the remaining pre-emulsion C and an aqueous solution of 0.18 parts by weight of ascorbic acid and 0.28 parts by weight of triethanolamine (dissolved in 5 parts by weight of water) to the reactor dropwise simultaneously, and controlling the dropping time to be 3.8 hours;

[0099] (7) After the addition is complete, keep the reaction warm for 1 hour;

[0100] (8) cooling to 50° C., adding 0.7 parts by weight of polyethylene glycol diglycidyl ether, and reacting for 30 minutes;

[0101] (9) The mixture was cooled to room temperature and the pH was adjusted to 8.2 with 0.7 parts by weight of aqueous ammonia.

[0102] Comparative Example 1: High-performance acrylic emulsion lacking functional monomers (corresponding to Example 1)

[0103] This comparative example lacks 2-hydroxy-3-phenoxypropyl methacrylate to demonstrate its importance to the emulsion performance.

[0104] Components:

[0105] 45 parts by weight of methyl methacrylate, 43 parts by weight of butyl acrylate, 2 parts by weight of methacrylic acid, 0.2 parts by weight of thioglycolic acid, 0.8 parts by weight of sodium lauryl sulfate, 0.6 parts by weight of alkylphenol polyoxyethylene ether, 0.3 parts by weight of ammonium persulfate, 0.1 parts by weight of ascorbic acid, 0.2 parts by weight of triethanolamine, 0.5 parts by weight of polyethylene glycol diglycidyl ether, 0.5 parts by weight of aqueous ammonia, and the balance to 100 parts by weight of water.

[0106] Preparation method:

[0107] Steps (1) to (9) are the same as those in Example 1, except that 2-hydroxy-3-phenoxypropyl methacrylate is not added in step (1), and the amount of butyl acrylate is increased accordingly.

[0108] Comparative Example 2: High-performance acrylic emulsion replacing the chain transfer agent (corresponding to Example 2)

[0109] In this comparative example, n-dodecyl mercaptan is used to replace thioglycolic acid to verify the special effect of thioglycolic acid as a chain transfer agent.

[0110] Components:

[0111] Same as Example 2, except that 0.3 parts by weight of thioglycolic acid was replaced by 0.3 parts by weight of n-dodecyl mercaptan.

[0112] Preparation method:

[0113] Steps (1) to (9) are the same as those in Example 2, except that 0.3 parts by weight of n-dodecyl mercaptan is used instead of thioglycolic acid in step (1).

[0114] Comparative Example 3: High-performance acrylic emulsion with excessively high functional monomer content (corresponding to Example 3)

[0115] In this comparative example, the content of 2-hydroxy-3-phenoxypropyl methacrylate is increased to verify its optimal dosage range.

[0116] Components:

[0117] 45 parts by weight of methyl methacrylate, 35 parts by weight of butyl acrylate, 18 parts by weight of 2-hydroxy-3-phenoxypropyl methacrylate, 4 parts by weight of methacrylic acid; other components are the same as those in Example 3.

[0118] Preparation method:

[0119] Steps (1) to (9) are the same as those in Example 3, except that the ratio of the monomers is adjusted in step (1).

[0120] Comparative Example 4: High-performance acrylic emulsion lacking a crosslinking agent (corresponding to Example 4)

[0121] In this comparative example, polyethylene glycol diglycidyl ether was not added to verify the effect of the cross-linking agent on the properties of the emulsion.

[0122] Components:

[0123] Same as Example 4, but without adding 0.7 parts by weight of polyethylene glycol diglycidyl ether.

[0124] Preparation method:

[0125] Steps (1)-(7) and (9) are the same as in Example 4, and step (8) is omitted.

[0126] Comparative Example 5: High-performance acrylic emulsion with incomplete redox initiation system (corresponding to Example 1)

[0127] This comparative example lacks triethanolamine to demonstrate the importance of a complete ternary redox initiation system.

[0128] Components:

[0129] The same as Example 1, but without adding 0.2 parts by weight of triethanolamine.

[0130] Preparation method:

[0131] Steps (1) to (9) are the same as in Example 1, except that triethanolamine is not added in step (6).

[0132] Comparative Example 6: High-performance acrylic emulsion with a single emulsifier system (corresponding to Example 2)

[0133] This comparative example uses only anionic emulsifiers to verify the synergistic effect of the composite emulsifier system.

[0134] Components:

[0135] The same as Example 2, but instead of adding 0.75 parts by weight of alkylphenol polyoxyethylene ether, the amount of sodium lauryl sulfate was increased to 1.75 parts by weight.

[0136] Preparation method:

[0137] Steps (1) to (9) are the same as those in Example 2, except that only 1.75 parts by weight of sodium lauryl sulfate is added in step (2).

[0138] Based on the core innovations and mechanisms of action of this invention, we designed the following models to evaluate the effectiveness of the solution:

[0139] 1. Particle size distribution test: Dynamic light scattering (DLS) was used to determine the average particle size and polydispersity index (PDI) of the emulsion particles.

[0140] 2. Solid content determination: The solid content of the emulsion was determined by the drying method.

[0141] 3. Glass transition temperature (Tg) test: Differential scanning calorimetry (DSC) was used to measure the Tg of the polymer.

[0142] 4. Water resistance test: The water resistance of the film after formation is determined by the immersion method.

[0143] 5. Adhesion test: Use the cross-hatch method to measure the adhesion of the coating on metal and plastic substrates.

[0144] 6. Weather resistance test: Use QUV accelerated aging tester for weather resistance test.

[0145] 7. Mechanical properties test: Use a universal testing machine to measure the tensile strength and elongation at break of the coating. Experimental method steps:

[0146] 1. Particle size distribution test:

[0147] Dilute the emulsion sample to 0.1% concentration

[0148] Testing with the Malvern Zetasizer Nano ZS

[0149] Test temperature: 25℃, repeat the test 3 times and take the average value

[0150] 2. Solid content determination:

[0151] Weigh about 2g of emulsion sample into an aluminum foil pan.

[0152] Dry in oven at 105°C for 2 hours

[0153] After cooling to room temperature, weigh and calculate the solid content

[0154] 3. Glass transition temperature (Tg) test:

[0155] The emulsion sample was prepared into a thin film and dried. The test was performed using TA Instruments DSC Q2000. The heating rate was 10 °C / min, and the temperature range was -50 °C to 150 °C.

[0156] 4. Water resistance test:

[0157] Apply the emulsion on the glass plate and dry for 24 hours

[0158] Immerse the coating in 25°C deionized water for 72 hours

[0159] Observe the changes in the coating appearance and rate it 1-5 (5 is the best)

[0160] 5. Adhesion test:

[0161] Apply the emulsion to metal and plastic substrates and let dry for 24 hours

[0162] Cross-hatch test according to ASTM D3359

[0163] Rating 0-5 (5 is best)

[0164] 6. Weather resistance test:

[0165] Apply the emulsion on the aluminum plate and dry it for 24 hours.

[0166] Tested using Q-Lab QUV accelerated weathering tester

[0167] Cycle: 4 hours UV-A irradiation (60°C), 4 hours condensation (50°C)

[0168] Total test time: 500 hours, observe the gloss retention rate of the coating

[0169] 7. Mechanical properties test:

[0170] Preparation of dumbbell-shaped specimens (ASTM D638 Type V)

[0171] Tensile testing using an Instron 5567 universal testing machine

[0172] Tensile rate: 50mm / min

[0173] The test results are shown in the following table:

[0174] Table 1. Emulsion performance test results

[0175]

[0176] According to the test results, Example 2 shows the best comprehensive performance and can be regarded as the best embodiment of the present invention. The present invention has the following unexpected technical effects:

[0177] 1. Excellent particle size control: The average particle size of Examples 1-4 is between 98-110 nm, and the PDI is less than 0.06, indicating that the emulsion has excellent monodispersity. This is attributed to the precise regulation of thioglycolic acid as a chain transfer agent and the efficient initiation of the ternary redox initiation system. The results of Comparative Examples 2 and 5 confirm this, and their particle size distributions are significantly broadened.

[0178] 2. Excellent water resistance and adhesion: Examples 2-4 received the highest ratings in both water resistance and adhesion tests. This is mainly due to the introduction of 2-hydroxy-3-phenoxypropyl methacrylate, whose hydroxyl groups provide strong substrate interactions and phenoxy groups enhance hydrophobicity. The results of Comparative Example 1 directly demonstrate the importance of this component.

[0179] 3. Excellent weather resistance: The gloss retention rates of Examples 1-4 are all above 92%, which is much better than that of the comparative example. This is because the phenoxy group of 2-hydroxy-3-phenoxypropyl methacrylate provides excellent UV absorption capacity, while the cross-linking effect of polyethylene glycol diglycidyl ether enhances the overall stability of the coating. The results of comparative example 4 verify the importance of the cross-linking agent.

[0180] 4. Balanced mechanical properties: Examples 1-4 show excellent balance between tensile strength and elongation at break. This is due to the synergistic effect of functional monomers, soft monomers and hard monomers, as well as the precisely controlled molecular weight distribution. Although Comparative Example 3 has higher tensile strength, its elongation at break is significantly reduced, indicating that too high a functional monomer content will lead to unbalanced performance.

[0181] 5. Efficient emulsion stability: The composite emulsifier system (anionic and nonionic) provides excellent emulsion stability, which is reflected in the smaller particle size and narrow distribution. Comparative Example 6 uses a single emulsifier, resulting in an increase in particle size and a wider distribution.

[0182] In summary, the present invention achieves the coordinated optimization of multiple key performance indicators through the carefully designed component ratio and preparation process. The introduction of 2-hydroxy-3-phenoxypropyl methacrylate, the precise regulation of thioglycolic acid, the efficient initiation of the ternary redox initiation system, and the cross-linking effect of polyethylene glycol diglycidyl ether jointly create a high-performance acrylic emulsion with excellent performance and wide application. This emulsion has great application potential in the fields of coatings, adhesives and waterproof materials.

[0183] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A high performance acrylic emulsion, characterized in that: Includes the following components: 45-50 parts by weight of main monomer, 35-40 parts by weight of soft monomer, 8-12 parts by weight of functional monomer, 2-4 parts by weight of carboxyl functional monomer, 0.2-0.4 parts by weight of chain transfer agent, 1.4-2.1 parts by weight of composite emulsifier, 0.6-1.0 parts by weight of redox initiator system, 0.5-0.8 parts by weight of crosslinker, 0.5-0.8 parts by weight of pH adjuster, and the balance is up to 100 parts by weight of water; wherein the functional monomer is used to improve the adhesion and weather resistance of the emulsion to the substrate; the chain transfer agent is used to control the molecular weight distribution and particle size distribution of the emulsion; the redox initiator system is used to improve the monomer conversion rate; the crosslinker is used to improve the water resistance and mechanical strength of the emulsion after film formation.

2. The high performance acrylic emulsion according to claim 1, characterized in that The main monomer is methyl methacrylate, the soft monomer is butyl acrylate, the functional monomer is 2-hydroxy-3-phenoxypropyl methacrylate, and the carboxyl functional monomer is methacrylic acid.

3. The high performance acrylic emulsion according to claim 1, characterized in that The chain transfer agent is thioglycolic acid.

4. The high performance acrylic emulsion according to claim 1, characterized in that The composite emulsifier comprises 0.8-1.2 parts by weight of anionic emulsifier and 0.6-0.9 parts by weight of nonionic emulsifier.

5. The high performance acrylic emulsion according to claim 4, characterized in that: The anionic emulsifier is sodium lauryl sulfate, and the nonionic emulsifier is alkylphenol polyoxyethylene ether.

6. The high performance acrylic emulsion according to claim 1, characterized in that: The redox initiation system comprises 0.3-0.5 parts by weight of an oxidative initiator, 0.1-0.2 parts by weight of a reducing agent and 0.2-0.3 parts by weight of an activator.

7. The high performance acrylic emulsion according to claim 6, characterized in that: The oxidative initiator is ammonium persulfate, the reducing agent is ascorbic acid, and the activating agent is triethanolamine.

8. The high performance acrylic emulsion according to claim 1, characterized in that: The cross-linking agent is polyethylene glycol diglycidyl ether, and the pH regulator is ammonia water.

9. A method for preparing the high-performance acrylic emulsion according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) mixing the main monomer, the soft monomer, the functional monomer and the carboxyl functional monomer, adding the chain transfer agent, and stirring to obtain a monomer mixture A; (2) dissolving the composite emulsifier in 80% of the water and stirring to obtain an emulsifier solution B; (3) slowly adding the monomer mixture A to the emulsifier solution B, and emulsifying at high speed for 10-15 minutes to obtain a pre-emulsion C; (4) adding 10% of the pre-emulsion C and 10% of the water into the reaction kettle and heating the kettle to 75-80° C.; (5) dissolving the oxidizing initiator in the redox initiation system in 5% of the water and slowly adding the solution to the reaction kettle to start polymerization; (6) simultaneously adding the remaining pre-emulsion C and the aqueous solution of the reducing agent and the activating agent in the redox initiation system to the reaction kettle, and controlling the adding time to be 3-4 hours; (7) After the addition is complete, keep the reaction warm for 1 hour; (8) cooling to 50° C., adding the cross-linking agent, and reacting for 30 minutes; (9) Cooling to room temperature, and adjusting the pH to 7.5-8.5 with the pH adjuster.

10. Use of the high performance acrylic emulsion according to any one of claims 1 to 8 in coatings, adhesives or waterproof materials.

Citation Information

Cited By

  • Polyacrylonitrile-based micro-nano hydrogel as well as preparation method and application thereof

    CN122465179A